Some Issues on the Turkic Part of Codex Cumanicus - Mollova, Mefküre (Prilozi za orijentalnu filologiju, 2017)
On the basis of the linguistic analysis of the Turkic language of the Codex Cumanicus, this work points out the imperfections of the tacitly supported concept that the authors of the Codex Cumanicus were of European origin (Italian and Germanic missionaries, who were leaming Turkic, i.e. Kumyk). It also initiates new problems regarding the origin of the composers, transcribers, correctors, and the commentator of the Turkic part of Codex Cumanicus, as well as the Solutions to the posed problems. When the language of Codex Cumanicus was defined, its scientific analysis was jeopardized by the statement that that it is the matter to Kipcac language, to the same extent, as well as the statement that it is “Turkish spoken by foreigners” (ecnebi Türkçesi). As the moment, the most acceptable would be the view that the author of Codex is of Kumyc origin. And the fact that the composers of Codex Cumanicus were Turkic, is supported by the preciseness of religious “Turkic-Chaman” wording, in the form that could not have been known to the foreigners. The analysis of the abbreviations and corrections in the transcripts of the manuscript has shown that the transcribers and correctors of the Turkic part of Codex Cumanicus were also Turkic; certain words were previously phonologically close to Uighur, while after the corrections were done, we get the impression that the corrector is of Kumyc Kipcac origin. The similar situation is with words that were previously close to hazar, while after the corrections they would be closer to their Chagatai “pronunciation”. Also, on the basis of transliteration of certain words, it is notable that certain graphemes for certain phonemes correspond to the phonemes of modem Uzbeg. Persian language in Codex Cumanicus is the version used by Turks, not the Persian spoken by the contemporary native Persians, which is proved by the linguistic properties of that part of vocabulary. Shorter German-Turkish pieces of text within Codex Cumanicus were most probably written by the Turks, who had spent some time leaming German in Europe, and this was not the authentic German language, used by the contemporary native German speakers. Turkic language (türkîce) in Codex Cumanicus was, most probably, the common written language used by Turkic peoples between 12* and 14* century. If we accept the fact that the European missionaries leamt and spoke Turkic, on the basis of the analysis of the translation, it is certain that they did not have any considerable role in the translation of Codex Cumanicus to Turkic, even though there are some indicators that there indeed was some joint work in the recording of certain information. It is worth mentioning that the previous title of this language was only Codex (meaning Collection), what is far more precise and, from a linguistic point of view, adequate title than the one given by Geza Kuun (Codex Cumanicus/Kumyc Collectioıî). The issues tackled by this work, together with numerous other problems and questions are stili öpen, what is proved by this study.